Performance of LED Employing Metal Oxide Mixed Thermal Interface Material by Structure Function Analysis - Shanmugan Subramani; Devarajan Mutharasu (Institute of Advanced Engineering and Science, 2013)
LED industries are currently focusing on the thermal management to reduce the junction temperature as well as the total thermal resistance for high power solid state lighting application. Metal powder or metal oxide filled thermal paste (TP) using as a thermal interface material is one kind of approach to solve the problem. In connection with that, milled TiO2 and Cr2O3 powder were mixed in different ratio with commercial thermal paste. Cumulative structure function (CSF) analysis was used to characterize the metal oxide mixed thermal paste as thermal interface material (TIM) for 3W LED. TiO2 mixed TIM showed good performance on reducing junction temperature (ΔTJ = 1.19 ºC) for driving current at 350 mA. Overall, TiO2 mixed TP shows low value of board to heat sink thermal resistance (Rth-b-hs) compared to all other results. Energy Dispersive Spectrum (EDS) analysis results revealed the percentage of mixed powder as low when compared with mixed ratio. O2 content in mixed paste showed immense effect on reducing total thermal resistance.DOI: http://dx.doi.org/10.11591/ijpeds.v3i4.4150